Early Neoproterozoic well-preserved stromatolites from southern Liaoning, North China: characteristics and paleogeographic implications - Zhang, Yong-Li; Lai, Guan-Ming; Gong, En-Pu; Wilson, Mark A.; Huang, Wen-Tao; Guan, Chang-Qing; Yuan, Ding-Cheng (Palaeoworld, 2023)
We report morphology and microstructure of the stromatolites of the Ganjingzi Formation in southern Liaoning. Sedimentologic and morphologic analyses indicate that the lower stromatolite mounds formed in a transgressive succession, while the stromatolite columns in the more complex upper biostrome changed vertically from dispersed growth to dense clumping. Biostratigraphic analysis shows that the stromatolites in the Ganjingzi Formation are similar to those from coeval strata in the Xuzhou-Huainan Region and in southern Jilin. Comparisons of the morphotype genera of stromatolites and the sedimentary setting between different areas, imply that sea-level was fluctuating in the east of the North China Craton (NCC) during the Ganjingzi interval and that the transgressions were beneficial to stromatolite growth, as indicated by the increased number of stromatolites in the study area.